Tantangan Pendidikan Karakter Berbasis Pondok Pesantren Di Era Media Sosial - Moh. Soleh Abdul Wahid; Ujang Imamul Mutaqin (CV. Biha Cendekia, 2026)
The purpose of this study is to determine how Islamic boarding school-based character education is implemented in the current era of social media. This study is a library research study with a conceptual-critical analysis approach. The focus of the research is directed at examining the challenges of Islamic boarding school-based character education in the social media era through the search and analysis of relevant scientific literature. Data collection was conducted through a systematic literature search using relevant keywords, followed by data selection and classification according to the study's focus related to Islamic boarding school-based character education in the social media era. Education today, supported by rapid technological advancements, has become a tool for educators in shaping character and developing skills, personality, knowledge, and insight for students, especially in Islamic boarding schools.